Perencanaan Pengendalian Banjir Kali Kedunglarangan Kabupaten Pasuruan - Aprilia Gita Permata; Novie HANDAJANI; Iwan Wahjudijanto (Universitas Jember, 2022)
Bangil Subdistrict in Pasuruan Regency, East Java contains the Kedunglarangan River with a length of 39.69 km and the Kedunglarangan Watershed (DAS) covering an area of ​​324.01 km². The inability of the drainage channel which is unable to accommodate the upstream water flow causes flooding in the Kedunglarangan River. This happened due to heavy rains that inundated several areas, one of which was in Kalianyar Village. This study aims to determine the planning of flood control management in the area. The method used for flood management in this study will be carried out by analyzing the design flood discharge with a return period of 25 years and the channel capacity analysis using HEC_RAS. The analysis was used for planning the addition of the embankment height in each river segment to reduce flood discharge. The results in this study were obtained by adding the height of the embankment in segment 1 with a discharge (Q) of 254.404 m3/s, carried out by adding an addition to the height of the left embankment by 4 m and the right side of the embankment with a height of 3.5 m, Segment 2 with river water discharge 550,839 m3/s, the addition of the height of the embankment on the left and right sides is 6.5 m and 4 m, respectively and segment 3 with a river water discharge of 680,997 m3/s, is done by adding the height of the embankment on the left and right by 5m and 2.5m. ABSTRAK Kecamatan Bangil di Kabupaten Pasuruan, Jawa Timur terdapat Kali Kedunglarangan dengan panjang 39,69 km dan Daerah Aliran Sungai (DAS) Kedunglarangan seluas 324,01 km². Ketidak mampuan saluran drainase yang tidak mampu menampung aliran air hulu menyebabkan banjir di Kali Kedunglarangan. Hal tersebut terjadi dikarenakan hujan deras yang menggenangi beberapa wilayah salah satunya pada Desa Kalianyar. Pada penelitian ini bertujuan untuk mengetahui perencanaan penanganan pengendalian banjir di daerah tersebut. Adapun metode yang dilakukan untuk penanganan banjir pada penelitian ini akan dilakukan dengan analisis debit banjir rancangan dengan kala ulang 25 tahun dan analisis kapasitas saluran menggunakan HEC_RAS . Analisis dilakukan pada debit rancangan digunakan untuk perencanaan penambahan tinggi tanggul pada setiap segmen sungai untuk mengurangi debit banjir. Hasil pada penelitian ini diperoleh dengan penambahan tinggi tanggul pada segmen 1 dengan debit (Q) sebesar 254,404 m3/dt, dilakukan dengan memberikan penambahan pada tinggi tanggul sebelah kiri sebesar 4 m dan sisi tanggul sebelah kanan dengan tinggi 3,5 m, Segmen 2 dengan debit air sungai 550,839 m3/dt, penambahan tinggi tanggul sisi kiri dan kanan masing-masing 6,5 m dan 4 m, masing-masing dan segmen 3 dengan debit air sungai 680,997 m3/dt, dilakukan dengan penambahan tinggi tanggul pada sisi kiri dan kanan sebesar 5m dan 2,5m.